A Novel GraphiteGraphite Dual Ion Battery Using an AlCl3[EMIm]Cl Liquid Electrolyte - Li, Z.; Liu, Jian; Niu, B.; Li, J.; Kang, F. (Wiley, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Herein, a novel graphite–graphite dual ion battery (GGDIB) based on a AlCl3/1-ethyl-3-methylimidazole Cl ([EMIm]Cl) room temperature ionic liquid electrolyte, using conductive graphite paper as cathode and anode material is developed. The working principle of the GGDIB is investigated, that is, metallic aluminum is deposited/dissolved on the surface of the anode, and chloroaluminate ions are intercalated/deintercalated in the cathode material. The self-discharge phenomenon and pseudocapacitive behavior of the GGDIB are also analyzed. The GGDIB shows excellent rate performance and cycle performance due to the high ionic conductivity of ionic liquids. The initial discharge capacity is 76.5 mA h g-1 at a current density of 200 mA g-1 over a voltage window of 0.1–2.3 V, and the capacity remains at 62.3 mA h g-1 after 1000 cycles with a corresponding capacity retention of 98.42% at a current density of 500 mA g-1. With the merits of environmental friendliness and low cost, the GGDIB has a great advantage in the future of energy storage application.